Pembuatan Kertas Komposit Berbahan Baku Tandan Kosong Kelapa Sawit dan Serabut Kelapa: Manufacture of Composite Paper Material from Palm Oil Palm Empty Fruits and Coconut Fiber - Pridata Gina Putri; Kurnia Rimadhanti Ningtyas; Taufik Nugraha Agassi (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2022)
Composite paper is paper made from a mixture of two or more kinds of paper pulp with other materials. The manufacture of composite paper in this study uses OPEFB as the basic material mixed with coconut fiber and uses cassava flour and banana flour as adhesives. Parameters observed in this study were physical and mechanical properties, cellulose, hemicellulose, and lignin from OPEFB composite paper and coconut fiber. Based on the results of this study, the highest mechanical physical properties of paper were thickness, grammage, and density with the addition of 20 gram cassava adhesive (1, 38 mm, 41, 78 g/m2, 0, 30 kg/m3 respectively) while the addition of banana flour had the highest mechanical physical properties at addition of 60 grams with thickness, grammage, and density (1, 49 mm, 45, 60 g/m2, 0, 30 kg/m3 respectively). As for the chemical characteristics of the paper on the adhesive cassava flour has the highest cellulose content in the addition of 20 grams of cassava flour (50, 83 %), while the treatment with the addition of banana flour has the highest cellulose content in the treatment of 60 grams (46, 76 %).